DAMPAK KEPUTUSAN INVESTASI DAN STRUKTUR KEPEMILIKAN KELUARGA TERHADAP KOMPENSASI DIREKSI PERUSAHAAN MANUFAKTUR INDONESIA - Surtihati Surtihati; Cynthia Afriani Utama (Jurnal Keuangan dan Perbankan, 2017)
This study examined the influence of family ownership structure and investment decisions on CEO compensation. This study also examined how the family ownership structure and investment decisions jointly affected CEO compensation. This study used 988 observations consisting of 150 manufacturing companies listed in Indonesia Stock Exchange from 2008 to 2014. The method used was fixed effects method (FEM). The results of the study showed that firms owned by a family gave higher compensation than non-family firms to their CEO. The family ownership structure proved the positive relationship between investment decisions and CEO compensation.